Teaching about the Spirit of Trust on Someone Who has Perception of Anomic Suicide: As a Solution to Generate Transcendental Trust on Personality - Syamsul Alam (Institut Teknologi Sepuluh Nopember, 2019)
Suicide is an event that often occurs among the community due to a personal psychological disorder, both due to depression, mental disorders and so on, especially depression due to economic, social and chronic diseases experienced by a person and lasts for a long time as a result they assume hat matters It inhibits all activities and life and even considers itself no longer useful because of the lack of intake of the values of the spirit of trust of his religion, as a result someone wants to end his life with suicide, the purpose of this study is to determine the effect of the teachings of belief (the spirit of trust) on anomic suicidal perceptions that aim to reduce the anomic suicide rate of a person in the community, the type of research used is library research by conducting a literature study both books, journals and other references relating to the object under study, based on the results of research that the teachings of trust (the spirit of trust) can reduce one's suicidal perceptions that have implications for reducing the desire to commit suicide.